(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2016)
In this article a novel by Graham Greene entitled Monsignor Quixote is analysed, a book that involves a recreation of the novel by Cervantes. The author of this article employs two concepts from Roman law: authority and power in his analysis. In this work by Greene, authority arises from the books or the book writers, whose reading allows life to keep making sense. In Greene, a strategy of reading known as the sortes virgilianae is found and this allows the characters to get their bearings in the daily difficulties. However, power is described as illiterate, the absence of books and ignorance